Kompetensi guru menyusun dan menerapkan RPP kurikulum 2013 dalam pelaksanaan pembelajaran melalui supervisi akademik teknik tagihan di SDN Sidomulyo 03 Kecamatan Ungaran Timur Kabupaten Semarang - Suwarti Suwarti (Universitas Sebelas Maret, 2020)
Abstract. The objective to be achieved in this study is the School Action Research aims to improve teacher competency in preparing and applying the 2013 Curriculum RPP into learning through the Academic Supervision of Engineering Bills in Sidomulyo StateElementary School 03. The research subjects in this study are class I teachers up to grade VI elementary school Negeri Sidomulyo 03 UPTD Pendidikan Ungaran Timur District, Semarang Regency are 6 (six) class teachers, namely: 6 class 1 to 6 class teachers. Techniques and data collection tools through interviews, observation, and documentation methods. I and Cycle II showed a good increase in teacher competence in the preparation and implementation of the 2013 Curriculum RPP in KBM. The results of the cycle 1 action compared to the pre cycle in the preparation of the Learning Implementation Plan (RPP) have increased. It was concludedthat academic supervision with billing techniques can improve teacher competency indeveloping and implementing the 2013 Curriculum RPP in implementing learning inSidomulyo 03 Public Elementary School, Ungaran Timur District, Semarang Regency in2017/2018 Academic Year.